Interferon‐free therapy in hepatitis C virus mixed cryoglobulinaemia: a prospective, controlled, clinical and quality of life analysis. Issue 4 (28th June 2018) - Gragnani, L.; Cerretelli, G.; Lorini, S.; Steidl, C.; Giovannelli, A.; Monti, M.; Petraccia, L.; Sadalla, S.; Urraro, T.; Caini, P.; Xheka, A.; Simone, A.; et al.
Summary: Background: Cryoglobulinaemic vasculitis (CV) is a lymphoproliferative disorder related to hepatitis C virus (HCV) infection; anti‐viral therapy is the first therapeutic option. CV can be incapacitating, compromising the patients' quality of life (QoL). In a controlled study, interferon‐based therapy was associated with a lower virological response in vasculitic patients than in patients without vasculitis. Limited, uncontrolled data on direct‐acting anti‐virals are available. Aim: To evaluate safety, clinical efficacy, virological response and the impact of interferon‐free treatment on QoL in HCV patients with and without mixed cryoglobulinaemia (MC). Methods: We prospectively studied HCV patients with cryoglobulinaemia (with vasculitis‐CV‐ and without vasculitis‐MC‐) and without cryoglobulinaemia (controls), treated with direct‐acting anti‐virals. Hepato‐virological parameters, CV clinical response and impact on QoL were assessed. Results: One hundred and eighty‐two HCV patients were recruited (85 with CV, 54 with MC and 43 controls). A sustained virological response at 12 weeks (SVR12) was achieved in 166 (91.2%) patients (77/85 CV, 48/54 MC, 41/43 controls). In CV SVR patients, cryocrit levels progressively decreased and clinical response progressively improved, reaching 96.7%, 24 weeks after treatment. QoL, baseline physical and mental component summaries were lower in the CV group compared to the other groups ( P < 0.05). Scores improved in all groups, and significantly in CV patients after SVR. Conclusions: No significant differences in SVR rates were recorded between cryoglobulinaemic patients and controls and a high clinical and immunological efficacy was confirmed in CV, supporting the role of interferon‐free therapy as the first therapeutic option. Interestingly, CV patients had worse baseline QoL than other HCV‐positive groups and interferon‐free therapy was effective in significantly increasing QoL, suggesting the important role of direct‐acting anti‐viral‐based therapy in improving CV's individual and social burden.